Automatic control, mechatronics and industrial engineering : proceedings of the International Conference on Automatic Control, Mechatronics and Industrial Engineering (ACMIE 2018), October 29-31, 2018, Suzhou, China /: proceedings of the International Conference on Automatic Control, Mechatronics and Industrial Engineering (ACMIE 2018), October 29-31, 2018, Suzhou, China. (2019) - Unknown
No abstract available